Trump 2.0 and the Pacific Island countries – what to expect? - Schleich, Anne-Marie (2025)
After the shock of the 2022 security agreement between China and the Solomon Islands, the United States increased its engagement with Pacific island countries. The next Trump administration is likely to focus on security issues with these countries. However, the biggest obstacle to improving relations will be their opposing stances on climate change. And the growing competition for power in the Pacific has given Pacific island leaders an opportunity to leverage their unique position.